Restorative Justice Approach in Handling Sexual Violence Criminal Cases (International Journal of Education and Literature, 2025)
This study examines the implementation of restorative justice approaches in handling sexual violence cases after the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS). Through a qualitative approach with empirical juridical design, the research was conducted using in-depth interviews with informants from the Legal Resource Center for Gender Justice and Human Rights (LRC-KJHAM) in Semarang and literature review. The findings reveal inconsistencies in the implementation of Article 23 of UU TPKS, which prohibits out-of-court settlements except for juvenile offenders. Law enforcement officers, particularly the police, still employ peaceful settlement approaches based on older regulations that contradict UU TPKS. This condition negatively impacts victims who often do not receive proper justice and recovery, and even experience revictimization. This research recommends that the government promptly develop more operational derivative regulations and enhance the capacity of law enforcement officers to adopt a victim-centered perspective.